Peningkatan Sikap Percaya Diri Warga Belajar melalui Kegiatan Project Class pada Program Paket C - Darmawan, Dadan; Handayani, Nurmila (Journal of Nonformal Education and Community Empowerment, 2019)
This study was conducted to find out how the application of project class activities in the PKBM Package C program at Kak Seto homeschooling, Bintaro, Jakarta. This research was conducted using qualitative methods in a descriptive form. The approach taken is to conduct observations, interviews, documentation, and also case studies. The subjects of the study were the tutor, head of the curriculum, and learner. It was concluded that the planning of project class program activities to improve the confidence of Kak Seto homeschooling is done by involving all elements involved including learning citizens. The implementation of the project class learning model gets a good response from students, with the enthusiasm and active participation in various activities carried out. The project class activities have an impact on increasing self-confidence in aspects of behavior, religious, and emotional.